Balance readjustment after different forms of exercise: A review - Zemkova, E. (International Journal of Applied Sports Sciences, 2009)
The study provides a review of our investigations on the effect of different forms of exercise on postural stability. Our findings showed that postural sway response to exercise depends on its type, intensity, and duration, however further studies are needed to investigate the role of different forms of muscle contraction and different activation of muscle fibers in its changes after exercise. As a possible physiological mechanisms of post-exercise balance impairment the following may be considered: fatigue, hyperventilation, deterioration of cutaneous, proprioceptive, vestibular, and visual inputs, muscle damage, dehydration, hyperthermia, dizziness, and so forth. In sports where impaired balance resulting from exercise may adversely affect the performance, both the magnitude of balance impairment in an initial phase of recovery and the speed of its readjustment should be taken in account. In theory, a decline of sway variables during recovery may be divided into three phases reflecting the effect of exercise on postural stability.